An Analytical Approach to Automotive Industry - Bulkan, Serol; YÜKSEKTEPE, FADİME ÜNEY; ÜLKÜ, İLAYDA (My University, 2015)
Inventory control helps to manage or locate materials and any information through the processes in the company. The aim of the inventory management in the companies is to optimize inventory control. Especially, for the manufacturing companies, inventory control has an important goal which satisfies the product to the customer on time. Therefore, the system in the production processes should not have any trouble during the production. This study aims to optimize the production system of a two stage production processes where the bumpers are produced for different type of cars and different colors due to the model of the car. In the first stage there are three injection machines which are parallel, and in the second stage, there is a dying station. A mixedinteger linear programming model is proposed to optimize the production process. With the proposed model, the production of the injection processes is optimized and the lot sizes for each stage are determined. Also, front and back bumpers for each same model is dyed concurrently which prevents the color difference for the same model of each type of car.

Malzemelerin ve iş süreçlerinin arasındaki herhangi bir bilginin yönetilmesi veya yerinin saptanması, envanter kontrolünden faydalanılarak yapılmaktadır. Şirketlerdeki stok yönetiminin amacı envanter kontrolünü eniyilemektir. Özellikle üretim yapan şirketler için envanter kontrolünün önemi büyüktür, çünkü müşterinin ürün talebini zamanında karşılaması gerekmektedir. Bu nedenle, üretim sırasındaki üretim süreçlerinde herhangi bir sorun olmamalıdır. Bu çalışma ile farklı model ve renkte üretilen otomobil tamponların iki aşamalı üretim süreçlerinin eniyilemesi hedeflenmektedir. İlk aşamada paralel durumdaki üç enjeksiyon makinesi, ikinci aşamada ise bir boyama istasyonu bulunmaktadır. Üretim sürecini eniyilemek için karma tamsayılı doğrusal programlama modeli önerilmektedir. Önerilen model ile enjeksiyon işlemlerinin üretimi eniyilenmiş olup, her aşama için parti boyutları belirlenmiştir. Ayrıca, her biri aynı model olan ön ve arka tamponların eşzamanlı boyanması sağlanarak, renk farklılıklarının oluşması önlenmiştir.
Otomotiv Sanayisine Yönelik Analitik Bir Yaklaşım
Keywords: Envanter Kontrolü; Parti Büyüklüğü; Karma-Tamsayılı Doğrusal Programlama; Inventory Control; Lot Size; Mixed-Integer Linear Programming